Nursing OSCEs : a complete guide to exam success - Caballero, Catherine , 1966- (Oxford University Press, 2012)
Complete guide to Objective Structured Clinical Examination (OSCE) success. Contains clear instructions for the 10 most common OSCE stations students may face. Includes over 60 photographs and interactive onlinematerial.--back cover